LISTA DOS NOMES POPULARES DOS RÉPTEIS NO BRASIL – PRIMEIRA VERSÃO - Castellari Gonzalez, Rodrigo; Diesel Abegg, Arthur; Matheus de Mello Mendes, Diego; Basto da Silva, Marcélia; Machado Filho, Paulo Roberto; Mario da Rosa, Conrado; Cunha Passos, Daniel; Vaz Ribeiro, Maurivan; Alves Benício, Ronildo; Oliveira, Jane C. F. (Herpetologia Brasileira, 2026)
Popular species names have always been based on human relationships with things around them, usually reflecting species’ external morphology, behavior or even the habitat they inhabit. In Brazil, the high number of popular names, in many cases for the same species, makes it difficult to comprehensively recognize these names, hampering communication between everyone interested in reptiles. This study presents a compilation of the popular names for the species of reptiles occurring in Brazil based on literature data. We listed 1264 popular names, 25 for Amphisbaenia, 29 for Crocodylia, 137 for Testudines, 301 for “Lizards” and 772 for Snakes. All Testudines and Crocodylia have popular names, however we found no popular names for three (4%) species of Amphisbaenia, 66 (24%) “Lizards” and 60 (15%) Snakes. Therefore, 15% of the 802 reptile species currently known in the country still have no popular names. Also, all species of Testudines and Crocodylia have exclusive popular names, nevertheless we found no exclusive names for 68 (92%) species of Amphisbaenia, 191 (69%) species of “Lizards” and 218 (53%) species of Snakes. This inventory is currently the most comprehensive effort to list the popular names of reptile species in Brazil.